REARING ENVIRONMENT AND FEEDING EQUIPMENT IN BRAZILIAN POULTRY PRODUCTION- A REVIEW - NEVES, DIEGO P.; NÄÄS, Irenilza de A.; BARACHO, Marta S. (Revista Brasileira de Engenharia de Biossistemas, 2010)
The last 30 decades were marked by an intensive poultry production, which reached a satisfactory level of production with the use of technology. These facts have allowed the country to stand out in a global setting, making the country the largest exporter and third largest producer of chicken meat in the world. This text provides a review on the subject of broilers’ rearing environment, and it presents feeders characteristics. Currently, projects related to rural equipment developed in Brazil have been studied only by Engineers and technicians, but could be optimized with the participation of designers.